Hydroxyapatite supported palladium catalysts for suzuki-miyaura cross-coupling reaction in aqueous medium - Indra, Arindam; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Catalysis Science & Technology, 2013)
Supported palladium catalyst 1 has been prepared by the immobilisation of [Pd(COD)Cl-2] (COD = 1,5-cyclooctadiene) on hydroxyapatite. Catalyst 2 has been prepared by subsequent reduction of catalyst 1 with sodium borohydride in ethanol. Under similar reaction conditions, catalyst 1 with Pd2+, is found to be almost five times more active than 2. Using 1 as the catalyst and water as the solvent, reaction conditions for Suzuki-Miyaura cross-coupling reactions have been optimised under aerobic conditions. The best catalytic activities are observed in the presence of potassium carbonate as the base and tetrabutylammonium bromide as a promoter. Catalyst 1 has been tested for catalytic cross-coupling reactions with sixteen different, electronically neutral, electron rich, electron poor and sterically hindered aryl boronic acids, and several different aryl halides including aryl chlorides. More than thousand turnovers and high selectivities to the hetero-coupled products have been observed in most cases. For many substrates the turnovers with 1 are notably more than what has been reported with other supported catalysts in water. The recyclability and scale-up potential of catalyst 1 have been tested and found to be satisfactory. A negligible drop in activity is observed over ten recycles with an accumulated turnover number of similar to 30000.